MODERN METHODS OF TREATMENT FOR HEMORRHAGIC VASCULITIS - Islamova Zulfiya Saidganixo'ja qizi (PEDAGOGS, 2024)
Vasculitis poses a great diagnostic, investigative and therapeutic challenge to the treating physician. The classification of vasculitides itself still eludes universal acceptance. Comprehensive management comprises establishing the diagnosis of true vasculitis after ruling out vasculitis mimics, finding the etiology if feasible, assessing the caliber of the vessels involved, deciphering the pathological process of vessel damage, investigating for the existence and extent of systemic involvement and finally planning the therapy in the background of co-morbidities. Successful management also entails regular monitoring to foresee complications arising from the disease process itself as well as complications of immunosuppressive treatment. Although steroids remain first line drug, biologics are emerging as popular agents in the treatment of immune-mediated vasculitis. Triphasic treatment is the best plan of action comprising induction, maintenance of remission and treatment of relapses.